Gestão integrada em sistemas de produção de carne: um levantamento das práticas no estado do Tocantins - Agnol, Mateus Dall’ (Universidade do Vale do Rio dos Sinos, 2016)
The dissertation aims to identify the main practices of integrated management for the meat chain. These practices are based on the ISO 9000 family requirements, ISO 14000 and ISO 22000 adopted by the meat processing industry in the state of Tocantins, northern Brazil. The major global markets and consumers are increasingly concerned about the way the meat is transported to human consumption. Earnings from exports approaching $ 8 billion, only if we refer to the year 2015 (ABIEC, 2015). The demands are increasing, new standards and import requirements are major challenges for the meat processing in Tocantins, Brazil and the world. The ISO certifications enable meat processors to adapt to these requirements, for the implementation of systems bring gains in Business Management (ISO 9001), improve food quality (ISO 22000) and foster care to mitigate environmental damage (ISO 14001). The traceability of the supply chain through the implementation of Radio Frequency Systems - RFID can bring greater competitive advantage with lower costs and better traceability of farm products to the table the final consumer. The processing studied adopt quality systems and ISO certifications, and use standard procedures or similar when supplying the domestic and international markets. This study seeks to contribute to the academic and industrial community, and production engineering, analyzing the management of beef cattle supply chain in Tocantins. For the development of this study, we used a case study as a methodological approach, and historical research based on literature review. This research presents a TQM Total Quality Management approach, which enabled display SCM (Supply Chain Management) in beef processing of Tocantins. The study was based on qualitative methodology and started with exploratory research and bibliographical review of the literature, using the CAPES portal. Subsequently, the data of the literature review were analyzed in order to identify the technical dimensions, technological and quality certifications in food production systems. From the identification of the main constructs, a pilot questionnaire was prepared which was submitted to three experts for validation and, after some adjustments, was used in the processing. The survey results were gathered and analyzed in the light of literature. Then the proposals were initiated, bringing contributions and suggestions for implementing improvements in the beef processing in Tocantins, as well as suggestions for future research on Quality Management System in the beef supply chain. The adoption of QMS, and a tool that brings control and standardization of processes allowing measurement of the effectiveness of actions taken, focusing on customer satisfaction and continuous improvement of processes, produces a differential to meat processors in the market, and constitute a practice in beef processing of the Tocantins state. This represents a major competitive advantage needed in the process of improving a company.
Keywords: Produção de carne; Gestão da qualidade; Sistema de gestão integrada; Rastreabilidade dos alimentos; Meat production; Quality management; Integrated management system; ISO certification; Food traceability; Certificação ISO; ACCNPQ::Engenharias::Engenharia de Produção